KETELANJANGAN DALAM SENI LUKIS INDONESIA: PERSPEKTIF KRITIK SENI RUPA - I Wayan ‘Kun’ Adnyana (SURYA SENI, 2009)
Nudity in the Indonesia Painting: Perspective of  Art Critics. Nude painting (art) is not something new in Indonesia. Many archaeological remains show how nudity, from its most sacred to its mundane forms, has existed in many cultures of this Nusantara archipelago.Although not all of the painters’ (artist’s) current creativity is inﬂ uenced by the custom of this ancient mystic culture, it can be said, however, that the creative heritage of these people of Nusantara who expressed nudity as a language of symbolicand religion languages: lingam-yoni for example, has had an inﬂ uence on these artists especially on the Balinese painters (artists).The creative principle, which obviously of a bigger inﬂ uence has been the tradition of nude painting as part of the teaching process of academic arts, which initially intended to strengthen the skill in anatomic rendition but later developed into a subject of visual art that challenge the artists’ independent creativity. Indeed, several Indonesian artists explore nudity very intensely as their language of expression. And several visual phenomena inherent in their works become widely recognized as artistic and conceptual achievements and receive awards from the global art community. It’s true that works with nudity as their subjects do not receive immediate acceptance from the publik. Some actually  experience conﬂ ict and even rejection; conﬂict which arises from the lack of agreement over the standard valuethat an art work has to be read solely from an artistic parameter.Reading the existing conﬂ ict on the one hand, and reﬂ ecting upon the enormous appreciation on the other, especially the recognition of concepts behind those works with subject of nudity, makes the research on Nudity in the Indonesian Paintings evermore urgent. Keywords: Indonesian Nude Painting and Eroticism